HUBUNGAN KARAKTERISTIK UMUR IBU DENGAN KECEMASAN IBU PRIMIGRAVIDA MENJELANG PROSES PERSALINAN DI KLINIK BERSALIN ELFARETTA BENGKULU - Amelia, Cevy; Sarmini, Sarmini; Irvani, Zendika (Universitas Batam, 2020)
Anxiety or commonly known as Anxiety is a sense of anxiety that arises because it feels there will be something unpleasant. Anxiety usually there are several factors that cause anxiety arises, such as biological, psychological, and social factors. Characteristics of a person also greatly affects anxiety, such as age, occupation, education, and parity. Primigravida mothers are prone to suffering anxiety and anxiety is very influential with the characteristics of a mother's age.This research type is quantitative, the design of this research is observational analytic, with approach of cross sectional, conducted in september 2017. Population in this research is primigravida mother at Bengkulu Elfaretta Maternity Clinic which amounted to 36 people. Sampling with proportional random sampling. The data obtained by using questionnaires to the respondents, then the data were analyzed univariat and bivariate with computer using Chi Square Statistical Test. The results showed that low-risk age was 38.9% and high risk was 61.1%. Primigravida mothers who experienced mild anxiety 36.1%, who experienced moderate anxiety 25.0%, while anxiety weight 38.1%. The results of statistical tests show (p = 0.013) means there is a Relationship between Age Characteristics with Primigravida Mother Anxiety before the birth process at Bengkulu Elfaretta Maternity Clinic in 2017.From the results of the study it can be concluded that there is a significant relationship between the characteristics of maternal age with primigravida mother's anxiety before the birth process at Bengkulu Elfaretta Maternity Clinic 2017.